Implementing Rainwater Harvesting for Sustainable Water Management in Faridpur, Bangladesh: Mitigating Pollution, Waterlogging, and Ensuring Safe Drinking Water - A. Gain; O. MD. Farque; S. Hosen (Iranica Journal of Energy and Environment)
Shortage of safe drinking water is a major problem in Bangladesh, especially during the dry season from November to March. Due to high population growth, the crisis of healthy drinking water is increasing day by day. Rainwater is a major source of pure drinking water. Rainwater harvesting has proven to be the most economical and environmentally friendly method. So, it can hold great potential to deal with the current problem of acute arsenic poisoning and pure water scarcity in Bangladesh. To overcome this problem a model rainwater harvesting (RWH) system has been demonstrated in Faridpur, Bangladesh. The research showed that by utilizing 1037 buildings as catchment areas and installing storage tanks in 20 unused spaces of government offices, it is possible to address the entire drinking water scarcity issue in Faridpur Municipality. The study also investigates the quality of local pipe-well water and the quality of the stored rainwater. The findings of present study showed the quality of harvested water is much better than the pipe-wells water. The runoff reduction through Rainwater Harvesting was 14.82% which can significantly reduce the water logging and water pollution problem of Faridpur city. The findings of this work provide a potential blueprint for expanding water access throughout Bangladesh and other countries facing similar challenges.